2016
DOI: 10.1038/srep27233
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Reversibility of DNA Methylation Induced by in vitro Grafting between Brassica juncea and B. oleracea

Abstract: Grafting between tuber mustard and red cabbage produced a chimeric shoot apical meristem (SAM) of TTC, consisting of Layers I and II from Tuber mustard and Layer III from red Cabbage. Phenotypic variations, which mainly showed in leaf shape and SAM, were observed in selfed progenies GSn (GS = grafting-selfing, n = generations) of TTC. Here the heritability of phenotypic variation and its association with DNA methylation changes in GSn were investigated. Variation in leaf shape was found to be stably inherited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 59 publications
(86 reference statements)
2
29
0
2
Order By: Relevance
“…Despite its long history and use in production and research, grafting‐induced variation, particularly in distant‐grafting systems, and its inheritance in progeny are not well understood. We previously investigated the exchange of heterologous sRNAs in grafting chimera (Li et al ., ), and the heritability and reversibility of grafting‐induced DNA methylation changes in sexual progeny has also been reported (Cao et al ., ). The primary aims of this current study were to determine whether grafting‐acquired changes in methylation are induced by changes in sRNAs profiles, and to establish how the epigenetic variations are maintained during cell propagation and regeneration.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Despite its long history and use in production and research, grafting‐induced variation, particularly in distant‐grafting systems, and its inheritance in progeny are not well understood. We previously investigated the exchange of heterologous sRNAs in grafting chimera (Li et al ., ), and the heritability and reversibility of grafting‐induced DNA methylation changes in sexual progeny has also been reported (Cao et al ., ). The primary aims of this current study were to determine whether grafting‐acquired changes in methylation are induced by changes in sRNAs profiles, and to establish how the epigenetic variations are maintained during cell propagation and regeneration.…”
Section: Discussionmentioning
confidence: 97%
“…Total sRNA tags were identified by BLAST analysis of the miRBase, GenBank, Rfam and Exon/Intron databases (Saxonov et al ., ; Meyers et al ., ; Benson et al ., ; Nawrocki et al ., ). The siRNAs were predicted using the tag2siRNA software (Cao et al ., ) and mapped to the DMGs via BLAST analysis of the NCBI database (http://blast.ncbi.nlm.nih.gov/Blast.cgi). The siRNA expression levels were normalized by the TPM value using the following formula: TPM = R1*1e6/total mapped reads (R1 represents the counts of a siRNA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression levels of DEGs were performed by qRT-PCR following the previously described method [52]. In brief, cDNA synthesis was performed using a PrimeScript RT reagent kit (Takara, Dalian, China).…”
Section: Validation Of Rna-sequence Data By Quantitative Real-time Pcmentioning
confidence: 99%
“…Then, we are wondering whether the genes from O and C are co-expressed in OCC, or only expressed one gene from one donor. Furthermore, in the graft chimeras Brassica juncea and B.oleracea, sequence analysis revealed that DNA methylation will affect the flowering time-and gibberellin response-related genes expressions, and may lead to the phenotypic variations in progenies [39]. According to the studies discussed above, chemical substances variations herein observed in OCC also suggested that whether the gene sequences of same gene in two donors were consistent, if not, will DNA methylation exist to influence chemical-related gene expression in OCC, and how these genes coordinate to regulate substances quantities are valuable to study more.…”
Section: Speculation Of Genetic Laws In Chimeras' Metabolitesmentioning
confidence: 99%